2000
DOI: 10.1016/s0895-7061(99)00184-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphism of the renin-angiotensin system associates with risk for lacunar infarction: The Ohasama study

Abstract: The polymorphism of the angiotensin-converting enzyme gene is considered to be associated with increased risk for stroke, but there is a diversity in the results obtained. The genetic involvement of the renin-angiotensin system in stroke also remains unclear. To predict the genetic risk of lacunar infarction, we conducted an association study in an Ohasama population, which is the cohort in a rural region of northern Japan. A total of 134 subjects without major neurological, cardiovascular, or metabolic disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 32 publications
0
65
0
1
Order By: Relevance
“…9 We reported that subjects with the DD genotype have a higher risk of restenosis after emergency percutaneous coronary transluminal angioplasity, 10 hypertension in males 11 and stroke. 12 We also reported that subjects with the AGT TT genotype are at higher risk for lacunar infarction 13 and history of hypertension, 14 but not stroke. 12 Indeed, the literature contains many reports from other laboratories about these genotypes and cardiovascular disease, but many of these results remain controversial.…”
Section: Introductionmentioning
confidence: 76%
“…9 We reported that subjects with the DD genotype have a higher risk of restenosis after emergency percutaneous coronary transluminal angioplasity, 10 hypertension in males 11 and stroke. 12 We also reported that subjects with the AGT TT genotype are at higher risk for lacunar infarction 13 and history of hypertension, 14 but not stroke. 12 Indeed, the literature contains many reports from other laboratories about these genotypes and cardiovascular disease, but many of these results remain controversial.…”
Section: Introductionmentioning
confidence: 76%
“…[13][14][15]18 Other studies reported the CC genotype to be associated with HTA, 19 coronary heart disease, 20 and stroke. 21 The A1166C polymorphism has been also studied in type 2 diabetic patients from India. 22 Interestingly, we found that diabetes and HTA were the most important risk factors for AMI in our population.…”
Section: Discussionmentioning
confidence: 99%
“…2). Even though we did not directly examine the volume of sodium intake and excretion in the Ohasama Study, the positive association between AGT polymorphism and non-dipper (17) or lacunar infarction (12) suggests that angiotensinogen might be involved in the pathogenesis of salt-sensitive hypertension.…”
Section: Angiotensinogen Gene Polymorphism and Cardiovascular Diseasementioning
confidence: 98%
“…Our previous investigations revealed that several clinical features that are mainly related to hypertension are associated with genetic variants of the angiotensinogen gene (AGT) ( Table 1) (9-16). The T235 allele in exon 2 or C 31 allele in exon 1 of AGT has been associated with increased risk for hypertension (9), positive family history of hypertension (10), coronary heart disease (11) and lacunar infarction (12). To elucidate the detailed relation between blood pressure and AGT polymorphism, we recently assessed the genetic involvement of the T 31C polymorphism on circadian rhythm of blood pressure variation in the Ohasama Study (17).…”
Section: Angiotensinogen Gene Polymorphism and Cardiovascular Diseasementioning
confidence: 99%